AGE AND GENDER-SPECIFIC MORPHOLOGICAL CHANGES IN FACIAL AREA CRANIOMETRIC INDICATORS AND FACIAL INDEX IN CHILDREN OF PRIMARY SCHOOL AGE - Adkhamov Sh. A (PT. Antis International Publisher, 2025)
Objective: This article studies the age- and gender-dependent morphological characteristics of the facial area and facial index in children of primary school age. Method: The study involved analyzing morphological characteristics with attention to age and sex variables in primary school children. Result: The results showed that certain changes in facial morphology are observed with age, as well as some statistically significant differences between the sexes. Novelty: These data are of great importance in pediatrics, pediatric dentistry, plastic and reconstructive surgery, and in the determination of anatomical features.